Accelerated Magnetic Seizure Therapy for Treatment of Major Depressive Disorder: A Report of 3 Cases. Issue 2 (June 2019) - Wang, Jian; Vila-Rodriguez, Fidel; Jiang, Wei; Ren, Yian-Ping; Wang, Chang-Ming; Ma, Xin
Abstract : Introduction: Major depressive disorder is a prevalent and debilitating condition that afflicts millions of people worldwide. Magnetic seizure therapy (MST) is a promising convulsive neurostimulation treatment for depression with fewer cognitive adverse effects than electroconvulsive therapy. Methods: A small case series of patients recruited as part of an open-label clinical trial is presented. Patients with depression underwent an accelerated MST protocol (aMST) consisting of 1 treatment per day for 6 consecutive weekdays. The primary outcome was severity on the HDRS17 (Hamilton Depression Rating Scale 17-item). In addition, patients underwent neuropsychological assessment with the Repeatable Battery for the Assessment of Neuropsychological Status and Stroop test. Results: After completing aMST, all patients experienced improvement. Two patients met response criterion, and the third experienced a 27% decrease on the HDRS17. All 3 patients experienced improvement in cognitive performance with a global 20% mean improvement and strongest improvement in immediate and delayed verbal memory indices (mean improvement of 40% and 27%, respectively). There were no cases of prolonged confusion or delirium after MST treatments. There were no severe adverse effects in any of the 3 patients. Conclusions: Accelerated MST protocol was well tolerated and associated with positive outcomes in this small case series. Accelerated MST protocol was not associated with prolonged confusion or delirium and was associated with improvement in memory indices. Our results merit further research in large RCT to test whether accelerated MST protocol might be an efficacious treatment for major depressive disorder.